2020
DOI: 10.1080/23802359.2020.1814173
|View full text |Cite
|
Sign up to set email alerts
|

The first mitochondrial genome of the relic Acanthobdella peledina (Annelida, Acanthobdellida)

Abstract: In this study, we assembled a complete mitochondrial genome of the Acanthobdella peledina sample from the Pitea River, Sweden. Thirty-six genes of the mitogenome sequence were identified, including 13 protein-coding genes (PCGs), 2 ribosomal genes (12S and 16S), 21 transport RNA genes, and 1 control region. The complete mitogenome is 14,640 bp long and A þ T biased (70.59%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Unfortunately, the vast majority of published checklists and other faunal papers on Arctic freshwater leeches does not contain morphological descriptions and images of specimens 22 , 24 , 31 and, hence, cannot be used as reliable sources of distribution data for Glossiphonia spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the vast majority of published checklists and other faunal papers on Arctic freshwater leeches does not contain morphological descriptions and images of specimens 22 , 24 , 31 and, hence, cannot be used as reliable sources of distribution data for Glossiphonia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Both the Kolguev Island and the Putorana Plateau are hard-to-reach areas, and none of freshwater leeches was collected from there before our sampling efforts. At first glance, this taxon may represent a high-latitude relict, as do two Acanthobdellidae species 27 , 30 , 31 , 97 . From an evolutionary point of view, the new genus may be a sister lineage to the Nearctic Actinobdella , having a similar sexannulate condition 36 , although external traits such as a specific annulation can arise independently in different clades of the glossiphoniid leeches 3 , 33 (see Supplementary Table S3 for detail).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with the paraphyly of Rhynchobdellida. Contrarily, the phylogenetic analysis based on the mitogenomes (Bolbat et al, 2020(Bolbat et al, , 2021, anchored hybrid enrichment (Phillips et al, 2019) and transcriptomes (Erséus et al, 2020) with more taxon sampling revealed the sister relationship between Glossiphoniidae and Oceanobdelliformes (only Piscicolidae in Erséus et al (2020)) and thus the monophyly of Rhynchobdellida.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies, such as our prior study, have incorporated other loci, such as 12S, 16S, and 28S (Tessler et al, 2018a;Bolbat et al, 2019). In addition to the Sanger data, a mitochondrial genome (Bolbat et al, 2020), ultraconserved element (UCE) data (Phillips et al, 2019a,b), and a transcriptome (Iwama et al, 2020) have recently been sequenced.…”
Section: Prior Phylogenetics Researchmentioning
confidence: 99%